2022
DOI: 10.1109/access.2022.3144406
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Style Image Super-Resolution Using Conditional Objective

Abstract: Recent studies have significantly enhanced the performance of single-image super-resolution (SR) using convolutional neural networks (CNNs). While there can be many high-resolution (HR) solutions for a given input, most existing CNN-based methods do not explore alternative solutions during the inference. A typical approach to obtaining alternative SR results is to train multiple SR models with different loss weightings and exploit the combination of these models. Instead of using multiple models, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Similar conclusions to the quantitative comparisons can be drawn from qualitative comparisons. We observe that all GAN-SR results including ESRGAN-FS [12], ESR-GAN+ [50], SPSR [40], RankSRGAN [67], LDL [31] and FxSR [47] produce visible artifacts and experience excessive sharpness. On the other hand, our method WGSR is able to reconstruct the genuine image details with high reconstruction accuracy including the regions with regular patterns and the areas containing fine details such as the light pink flowers on the bush (Fig.…”
Section: Comparison With the State-of-the-artmentioning
confidence: 84%
See 4 more Smart Citations
“…Similar conclusions to the quantitative comparisons can be drawn from qualitative comparisons. We observe that all GAN-SR results including ESRGAN-FS [12], ESR-GAN+ [50], SPSR [40], RankSRGAN [67], LDL [31] and FxSR [47] produce visible artifacts and experience excessive sharpness. On the other hand, our method WGSR is able to reconstruct the genuine image details with high reconstruction accuracy including the regions with regular patterns and the areas containing fine details such as the light pink flowers on the bush (Fig.…”
Section: Comparison With the State-of-the-artmentioning
confidence: 84%
“…Liang et al [31] suggested a locally discriminative learning framework LDL by externally computing a probability map of each pixel being artifacts based on patch-level residual variances. Park et al [47] introduced Flexible Style Image Super-Resolution (FxSR), which optimizes SR network with image-specific objectives without considering the regional characteristics. Later, in SROOE, Park et al [48] proposed optimal objective estimation depending on perceptual and objective image maps.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations